2014
DOI: 10.1371/journal.pone.0088446
|View full text |Cite
|
Sign up to set email alerts
|

Strawberry Flavor: Diverse Chemical Compositions, a Seasonal Influence, and Effects on Sensory Perception

Abstract: Fresh strawberries (Fragaria x ananassa) are valued for their characteristic red color, juicy texture, distinct aroma, and sweet fruity flavor. In this study, genetic and environmentally induced variation is exploited to capture biochemically diverse strawberry fruit for metabolite profiling and consumer rating. Analyses identify fruit attributes influencing hedonics and sensory perception of strawberry fruit using a psychophysics approach. Sweetness intensity, flavor intensity, and texture liking are dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
239
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(279 citation statements)
references
References 52 publications
16
239
1
3
Order By: Relevance
“…Soluble solid content has been regarded as an effective indicator of sweetness in fruit, with a total measurement of sucrose, glucose and fructose as the predominant soluble solids (Basson et al 2010). Previous reports also showed that the variation in sweetness intensity was well explained by sugar content (Schwieterman et al 2014). An approximately equal content (p > 0.05) of total sugar was observed in cultivars 'YueShi' and 'ChanSiWan' (Table 1), which explained their high similarity of taste (Fig.…”
Section: Sugarmentioning
confidence: 99%
See 1 more Smart Citation
“…Soluble solid content has been regarded as an effective indicator of sweetness in fruit, with a total measurement of sucrose, glucose and fructose as the predominant soluble solids (Basson et al 2010). Previous reports also showed that the variation in sweetness intensity was well explained by sugar content (Schwieterman et al 2014). An approximately equal content (p > 0.05) of total sugar was observed in cultivars 'YueShi' and 'ChanSiWan' (Table 1), which explained their high similarity of taste (Fig.…”
Section: Sugarmentioning
confidence: 99%
“…These chemical compositions in persimmon fruit are closely related not only to its flavour and sensory quality, but also to the nutritional properties and beneficial health effects of the fruit. It is commonly known that the contents of individual sugars as well as the sugar/organic acid ratio directly correlate with the sweetness of persimmon fruit (Schwieterman et al 2014). The colour of persimmon fruit in different cultivars varies from Highlights Five persimmon cultivars showed different aroma and taste.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable effort is currently being expended on strawberry breeding programs in order to develop new cultivars with enhanced flavor and health-related compounds (Vandendriessche et al, 2013). Overall strawberry liking is mainly influenced by sweetness and flavor intensity, which are undermined by environmental pressures that reduce sucrose and the total volatile compounds content (Schwieterman et al, 2014). Indeed, sucrose was proposed to be the metabolite with the single most significant contribution to the overall linking.…”
Section: Introductionmentioning
confidence: 99%
“…Foamy or emulsified structures, such as ganache or sabayon sauces, can lower perceived sourness, bitterness and astringency in products made with unsweetened pressed lingonberry juice, which has natural bitter, sour and astringent characteristics (Sandell et al, 2015). Interdisciplinary collaborations between sensory, nutrition, and plant scientists are key to producing palatable products that appeal to health conscious consumers and grown with agricultural practices that are sustainable, as has been as shown in optimizing tomatoes (Bartoshuk & Klee, 2013) and strawberries (Schwieterman et al, 2014). …”
Section: Discussionmentioning
confidence: 99%